Peningkatan Kompetensi Guru dalam Melaksanakan Praktikum Fisika pada Pembelajaran Jarak Jauh melalui Pelatihan Perangkat Analisis Video - Bintoro Siswo Nugroho; Zulfian Zulfian; Yudha Arman; Asifa Asri; Dwiria Wahyuni (Universitas Muhammadiyah Semarang, 2023)
The pandemic of COVID-19 has triggered awareness of the significant role of distance learning systems. Implementing science experiments, involving observation and measurement, requires more complex steps when conducted remotely online. An innovative method that can be used to address this issue is the combination of experimental demonstrations and video analysis. This article reports a training activity for the design and implementation of physics experiments using the video analysis software, Tracker, to improve the competence of physics teachers in conducting experiments through distance learning systems. The training was conducted through tutorials, demonstrations, practice sessions, work instructions, and online discussions. The impact of the training was measured by evaluating pre- and post-training questionnaires. The results indicate that the training can enhance participants' insights and competencies. This training provides an alternative solution for conducting laboratory experiments during face-to-face learning activity restrictions.